Is vibration exercise a useful addition to a weight management program? - Cochrane, D. J. (Scandinavian Journal of Medicine & Science in Sports, 2012)
Vibration exercise (VbX) has received a lot of attention as an exercise modality, which evokes muscular work and elevates metabolic rate that could be a potential method for weight reduction. Popular press has purported that VbX is quick and convenient, and 10 min of VbX is equivalent to 1 h of traditional exercise, where it has been marketed as the new weight-loss and body toning workout. However, research studies have shown that muscle activation occurs but the energy demand in response to VbX is quite low, where exhaustive VbX reported a metabolic demand of 23 mL/kg/min compared with 44 mL/kg/min from an exhaustive cycle test. Different vibration frequencies with varying amplitudes and loads have been tested, but only small increases in metabolic rate have been reported. Based on these findings, it has been indirectly calculated that a VbX session of 26 Hz for three continuous minutes would only incur a loss of ?10.7 g fat/h. Following a 24-week program of VbX, no observed differences were found in body composition, and following 12 months of VbX, the time to reach peak inline image was significantly higher in conventional exercise compared with VbX. However, one study has reported that percentage body fat decreased by 3.2% after 8 months after VbX in comparison with resistance and control groups that performed no aerobic conditioning. The evidence to date suggests that VbX can increase whole and local oxygen uptake; however, with additional load, high vibration frequency, and/or amplitude, it cannot match the demands of conventional aerobic exercise. Therefore, caution is required when VbX programs are solely used for the purpose of reducing body fat without considering dietary and aerobic conditioning guidelines.